If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -20 + 5x = -3 + -1x Solving -20 + 5x = -3 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -20 + 5x + x = -3 + -1x + x Combine like terms: 5x + x = 6x -20 + 6x = -3 + -1x + x Combine like terms: -1x + x = 0 -20 + 6x = -3 + 0 -20 + 6x = -3 Add '20' to each side of the equation. -20 + 20 + 6x = -3 + 20 Combine like terms: -20 + 20 = 0 0 + 6x = -3 + 20 6x = -3 + 20 Combine like terms: -3 + 20 = 17 6x = 17 Divide each side by '6'. x = 2.833333333 Simplifying x = 2.833333333
| 12z=1 | | 5000=10x^2+90x | | 4x-24=7x-28 | | .2x^2-.8x+.5=0 | | 3/4d-1/5=1/6 | | 8x-45=6x+54 | | x^(1/2)/2=343^(1/3) | | x(x-6)+9=25 | | 10.2+3n=11 | | X+.05x=294000 | | 10y-7=4y+5 | | -84=-2+6x+8+3x | | -7b=63 | | 2(u-2)-5u=-2(u+3) | | 4a=2a+1 | | 4x+5x+3+5x+6=107 | | 5x-9=87-7x | | 4x+2y+3z= | | 0=14x^2+x-4 | | 2x^2+48x+160=364 | | 10(z+3)-3(z-3)=2(z-1)+4(z-4) | | 28x-7-16x=3(4x-3)+2 | | ln(x+10)-ln(x+4)=3 | | -1/5×-9/7=-3/2 | | 96-33-(-109)= | | 6=-3(22-y)+2(y-4) | | 83-(6x+15)=6(x+7)+x | | in(x+10)-in(x+4)=3 | | 5a+7y+8a+7y= | | 2x^3+5x^2+x+3=621 | | 4x+5x+2+5x+7=107 | | 2x^3+5x^2+x-618=0 |